Reactive wetting of TA2 pure Ti and TC4 alloy by molten Al 4043 alloy at 873–973 K. (November 2017) - Lin, Qiaoli; Li, Fuxiang; Jin, Peng; Zhong, Weiqiang
Abstract: Wetting of typical industrial grades of Ti by Al 4043 alloy was studied by the sessile drop method at 873–973 K under high vacuum. Al/Ti is a typical reactive wetting system, and the double phases in TC4 alloy but only one phase in pure Ti caused the different interfacial structure. The mass transport was enhanced at liquid/solid interface due to the loosened Al3 Ti layer in Al/TC4, but the compact Ti7 Al5 Si12 layer would block the mass transport in Al/TA2 pure Ti, that further caused the different final wettability. The spreading dynamics of both TA2 and TC4 can be described by reaction product control model, and the activation energy is in the range of 10–47 kJ/mol, which is corresponding to the surface energy difference per molar area between Ti and TiO2 . Highlights: Wettability of TC4 alloy is better than TA2 pure Ti by molten Al 4043 alloy. Interfacial structures caused the different wettability. Intensity of mass transfer at interface is the key factor for improving wettability.